Antiviral response within different cell types of the CNS - Telikani, Zahra; Monson, Ebony A.; Hofer, Markus J.; Helbig, Karla J. (Frontiers in Immunology, 2022)
The central nervous system (CNS) is a constitutive structure of various cell types conserved by anatomical barriers. Many of the major CNS cell-type populations distributed across the different brain regions are targets for several neurotropic viruses. Numerous studies have demonstrated that viral susceptibility within the CNS is not absolute and initiates a cell-type specific antiviral defence response. Neurons, astrocytes, and microglial cells are among the major resident cell populations within the CNS and are all equipped to sense viral infection and induce a relative antiviral response mostly through type I IFN production, however, not all these cell types adopt a similar antiviral strategy. Rising evidence has suggested a diversity regarding IFN production and responsiveness based on the cell type/sub type, regional distinction and cell`s developmental state which could shape distinct antiviral signatures. Among CNS resident cell types, neurons are of the highest priority to defend against the invading virus due to their poor renewable nature. Therefore, infected and uninfected glial cells tend to play more dominant antiviral roles during a viral infection and have been found to be the major CNS IFN producers. Alternatively, neuronal cells do play an active part during antiviral responses but may adopt differential strategies in addition to induction of a typical type I IFN response, to minimize the chance of cellular damage. Heterogeneity observed in neuronal IFN responsiveness may be partially explained by their altered ISGs and/or lower STATS expression levels, however, further in vivo studies are required to fully elucidate the specificity of the acquired antiviral responses by distinct CNS cell types.